One Step Over the Line: Toward a History of Women in the North American Wests - Sheila McManus (The West Unbound:Social and Cultural Studies, 2008)
This eclectic and carefully organized range of essays-from women's history and settler societies to colonialism and borderlands studies-is the first collection of comparative and transnational work on women in the Canadian and U.S. Wests. It explores, expands, and advances the aspects of women's history that cross national borders. Out of the talks presented at the 2002 "Unsettled Pasts: Reconceiving the West through Women's History," Elizabeth Jameson and Sheila McManus have edited a foundational text with a wide, inclusive perspective on our western past.